Conversation Implicature in Spongebob Squarepants: Your Shoe’s Untied Animation - Prasojo, Teguh Iman; Bustam, Muhammad Rayhan (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
A research entitled Conversation Implicature in Spongebob Squarepants: Your Shoe’s Untied Animation aim to find the type, function of implicature, and context that found in this animation and explain or describe the type, function of implicature and context. The source taken from the transcript of SpongeBob Squarepants: Your Shoe’s Untied. The writer uses Yule and Searle theory which Yule is to identify types of implicature found in the animation and Searle to find the function of implicature found in the animation. This analysis uses qualitative descriptive method. Results found in this analysis are that there are 2 data using general implicature, 2 data using particularized implicature, and 1 data using scale implicature. Keywords: Pragmatics, Implicature, Meaning, Spongebob Squarepants